Exploring the role of inflammation in major depressive disorder: beyond the monoamine hypothesis - Pastis, Irene; Santos, Melody G.; Paruchuri, Akshita (Frontiers in Behavioral Neuroscience, 2024)
Major depressive disorder affects approximately 8.4% of the United States population. The World Health Organization estimates that 280 million adults worldwide are suffering from depression. They have estimated that by 2030 it will be the second most serious condition. Current treatment relies on the monoamine hypothesis, however, one-third of patients with MDD do not respond to monoamine-based antidepressants. For years, it was hypothesized that the primary pathway of MDD involved serotonin as the main neurotransmitter. The monoamine hypothesis, a widely accepted theory, sought to explain the biological basis of MDD as being caused by the depletion of monoamine neurotransmitters, namely norepinephrine and serotonin. This hypothesis regarding monoamines as the pathophysiological basis of MDD led to the design and widespread use of selective serotonin reuptake inhibitors. However, given that only one-third of patients improve with SSRI it is reasonable to infer that the pathway involved is more complex than once hypothesized and there are more neurotransmitters, receptors, and molecules involved. The monoamine hypothesis does not explain why there is a delay in the onset of effect and action of SSRIs. Several studies have demonstrated that chronic stress is a risk factor for the development of MDD. Thus the monoamine hypothesis alone is not enough to fully account for the pathophysiology of MDD highlighting the need for further research involving the pathways of MDD. . In this paper, we review the role of inflammation and cytokines on MDD and discuss other pathways involved in the development and persistence of depressive symptoms.